PERENCANAAN STRUKTUR APARTEMEN WARHOL RESIDENCES SEMARANG - Mardani Rizki Anggoro; Monica Devi; Nuroji Nuroji; Rudi Yuniarto Adi (Jurnal Karya Teknik Sipil, 2013)
Warhol Residences Apartment is one of the candidates for the skyscrapers that will soon be built in strategic areas Simpang Lima Semarang. These Apartments are located at No. 137 Ahmad Yani Street Semarang. By carrying out the minimalist and modern design, these apartments are expected to meet the needs of the residents of Semarang and foreigner the comfortable dwelling. In this thesis, Warhol Residences apartment’s structure is designed based on the method SRPMK or Special Moment Frame Structure bearers. The main guidelines in this plan are taken from Concrete SNI 03-2847-2002 and RSNI 03-1726-2010 Earthquake. The modeling is made, performed using software Extended Three-Dimensinal Analysis of Building Systems (ETABS) version 9.2.7. Beside that, it also use some other kind of supporting software such as Structure Analysis Program 2000 (SAP 2000), PCACOL, and Auto Cad. Some work items are taken into account include the overall structure of the work of both Primary and Secondary element. Primary structural elements include: Beams, High Beams, Columns, Shearwall / Corewall, joint and Bore Pile Foundation. While the secondary elements are: the plates, and the plate Basement Walls, Stairs, Ramp, and Lift. The analysis showed that the structure of the apartment safe and capable Warhol Residences accounted for analytically.